Fixed Bicycle System Gamification in order to Improve Student's Physical Condition and Generate Energy (Action research) - Pouya Khani; Salman Goli-Bidgoli; Mostafa Heshmat; Marjan Moazzam-Sedeh (Vesnu Publications, 2020)
Introduction: Today, with the advancement of technology and the expansion of the use of computers and mobile phones, mobility and health care through gamification has reached a special place. Despite increasing people health, gamification can create a small step towards a green city and create new job opportunities. Materials and Methods: In this study, a motor was attached to the pedal or rotary axis of a stationary bicycle as a generator to convert the produced mechanical energy into the electrical form. Some buttons were also mounted on the bicycle handlebar so that the user could control the game character in the Android application. All required hardware and circuits were also initially selected and designed to provide the power needed to charge the mobile and send the sensor information to the software via a Bluetooth module. Results: Referring to the latest achievements in health care, the complete design and manufacturing process of the control hardware required to read the information of the sensors connected to the bicycle and send them by a microcontroller to a mobile application as well as the design of a related android game with its software challenges, were provided. Two IoT-based Android developing tools, Flutter and Flame, were also briefly introduced. Conclusion: The output of this study was a full version of a small-scale stationary bicycle attached to the sensor, which was a comprehensive example of a set of interconnected bicycles. It can be widely used at sports clubs, parks, and gardens to enhance sport culture through gamification.